Convention collective — Validité de certaines clauses — Caractère légal d'un arrêt de travail destiné à les respecter (Relations industrielles / Industrial Relations, 1962)
Summary1. A clause in a labour agreement, according to which an employer undertakes not to require an employee to work on domestic nonunion shop goods, or on goods imported from a specified country is perfectly legal and valid.2. A refusal on the part of employees to carry out work which an employer would require them to carry out in violation of such a clause would not constitute an illegal stoppage of workThe Association of Millinery Manufacturers vs The United Hatters Cap and Millinery Workers International Union, Local No. 49; Judge Emile Trottier of the Court of Sessions of the Peace, single arbitrator. A.L. Stein, Q.C., counsel of the Association, and Me Philip Cutler, counsel for the Union, Private arbitration.